1998
DOI: 10.1097/00002030-199818000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Increased protected sex and abstinence among Namibian youth following a HIV risk-reduction intervention

Abstract: There is evidence that the 'My Future is My Choice' (MFMC) intervention is reducing HIV risk behaviours among sexually inexperienced participants aged 15-18. Related risk behaviours and perceptions are also positively impacted by the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 13 publications
2
113
2
1
Order By: Relevance
“…However, a comparison between respondents who received life skills or life orientation education and condom use showed that condom use was much lower amongst respondents who received life skills or life orientation education (23.3%) than those who did not (76.7%). These findings are contrary to those of a study conducted by Stanton, Kahihuata, Fitzgerald, Neumbo, Kanduuombe and Ricardo et al (1998:2474-2475) amongst young people who followed the 'My future is my choice' programme at Namibian schools, and which indicated a marked reduction of sexual risk behaviours, increased condom use and knowledge about HIV and AIDS amongst young people who had followed the programme.…”
Section: Educational Background Of Respondentscontrasting
confidence: 97%
“…However, a comparison between respondents who received life skills or life orientation education and condom use showed that condom use was much lower amongst respondents who received life skills or life orientation education (23.3%) than those who did not (76.7%). These findings are contrary to those of a study conducted by Stanton, Kahihuata, Fitzgerald, Neumbo, Kanduuombe and Ricardo et al (1998:2474-2475) amongst young people who followed the 'My future is my choice' programme at Namibian schools, and which indicated a marked reduction of sexual risk behaviours, increased condom use and knowledge about HIV and AIDS amongst young people who had followed the programme.…”
Section: Educational Background Of Respondentscontrasting
confidence: 97%
“…Five were delivered by both teachers and peers (not shown in Table 22). 51,58,63,68,71 Two of the studies, Levy and colleagues 65 and Coyle and colleagues, 61 which fell into the 'Other' category, used specially trained health educators. One study, Jemmott and colleagues, 43 used a specially trained 'adult facilitator'.…”
Section: Chaptermentioning
confidence: 99%
“…Only one study, Wight and colleagues 70 mentioned including the promotion of local sexual health services (either by the 69 used a longdistance interactive televised format to deliver their intervention to some of the participants. Components in the 'Other' category included the use of games (Stanton and colleagues, 68 Stephenson ) both aimed to improve the quality of young people's sexual relationships.…”
Section: Content Of the Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, raising awareness of HPV infection among women can help avoid/reduce high-risk sexual behaviors (Shepherd et al, 2000;Zhang et al, 2011), increase self-protection in sexual activities (Stanton et al, 1998), and promote client-initiated cancer screening (Stone et al, 2002). It is anticipated that health education, integrated with prevention, early detection and appropriate treatment will save millions of women's lives from cervical cancer in resource-constrained settings in China, Middle and Far East regions and sub-Saharan Africa among many other countries in the long-term (IARC, http://globocan.iarc.fr/fact_sheets_cancer.aspx).…”
Section: Introductionmentioning
confidence: 99%